2018
DOI: 10.1177/2374373518769008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Language Barriers on Quality of Care and Patient Safety for Official Language Minority Francophones in Canada

Abstract: Introduction: The risks to patient safety and quality of care faced by members of linguistic minority groups have been well-documented. However, little research has focused on the experience of official language minorities in Canada. Methods: This multiple method study (online and paper-based surveys combined with semi-structured individual interviews with patients and interpreters-health navigators) explored the experience of minority Francophones living in 4 Canadian provinces. Results: Patients and interpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
109
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(121 citation statements)
references
References 43 publications
6
109
0
6
Order By: Relevance
“…However in Nepal, this is impaired by short consultation times and limited skills of practitioners in behavioural management. These barriers were identified in the previous studies from Nepal and other settings38–41 and could negatively affect the patient’s ability to communicate and to understand the information effectively, resulting in poor patient’s engagement in self-management 42–45. Similarly, there was inadequate motivational support from the provider side to encourage patients in shared decision-making, health-related behaviours and self-management.…”
Section: Discussionmentioning
confidence: 99%
“…However in Nepal, this is impaired by short consultation times and limited skills of practitioners in behavioural management. These barriers were identified in the previous studies from Nepal and other settings38–41 and could negatively affect the patient’s ability to communicate and to understand the information effectively, resulting in poor patient’s engagement in self-management 42–45. Similarly, there was inadequate motivational support from the provider side to encourage patients in shared decision-making, health-related behaviours and self-management.…”
Section: Discussionmentioning
confidence: 99%
“…Communication barriers can be exacerbated by language discordance [13], which occurs when a patient and their provider lack proficiency in a shared language. Language discordance can negatively impact access to healthcare services, quality of healthcare services, and patient outcomes [14,15]. Previous studies have shown that residents who live in minority language situations face barriers when accessing healthcare services [16,17], have longer emergency department visits and hospitals stays [18,19], have higher rates of hospital admissions and re-admissions [20][21][22], and experience more harmful events in hospitals [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…There is some precedent for an association between patient language and patient harm: Patients with limited English proficiency may experience more severe adverse events than patients whose primary language is English, and the errors experienced by non-English speaking patients are more likely to be attributed to communication failure. 30,31 We speculate that non-English-language-speaking patients may experience challenges related to catheter maintenance practices that English-speaking patients (and their families) do not experience. For example, nursing discussions with patients and families about the importance of daily chlorhexidine bathing, or the need to keep soft limb restraints in place to ensure a patient does not inadvertently dislodge or disconnect a catheter, may be more difficult if the team is having to wait on the arrival of an interpreter or may be truncated if conducted via interpreter telephone service.…”
Section: Discussionmentioning
confidence: 98%